Direct effect of urea and vermicompost on growth and seed yield of bottle gourd and their residual effect on succeeding carrot - Bairwa, L.N.; Khandelwal, S.K. (Annals of Agricultural Research, 2016)
A field experiment was conducted to ascertain the influence of urea and vermicompost on growthand seed yield of bottle gourd and their residual effect on succeeding carrot crop at AgricultureResearch Station, Durgapura, Jaipur during 2004-05 and 2005-06. The recommended dose of nitrogen(RDN) was supplied through urea and vermicompost in different combinations. It was found thatintegrated use of nitrogen significantly influenced the growth, yield attributing characters, yieldand nutrient content in seed. 50% RDN through urea and 50% RDN through vermicompost wasfound to be the most significant not vine length, number of primary branches, fruit length andgirth, number of fruits (2.99) per vine, number of seeds (464.3) per fruit and seed yield (1012.5 kg/ha). After harvest of bottlegourd seed crop, carrot was sown on layout with recommended packageand practices. It revealed that 100% RDN through vermicompost recorded maximum root length,root width and yield of succeeding carrot crop.